The Edinburgh history of reading : subversive readers - Rose, Jonathan, 1952- (The Edinburgh History of Reading, 2020)
Subversive Readers explores the strategies used by readers to question authority, challenge convention, resist oppression, assert their independence and imagine a better world. This kind of insurgent reading may be found everywhere: in revolutionary France and Nazi Germany, in Eastern Europe under Communism and in Australian and Iranian prisons, among eighteenth-century women reading history and nineteenth-century men reading erotica, among postcolonial Africans, the blind, and pioneering transgender activists.